Chiglitazar alleviates cognitive dysfunction in diabetic mice by restoring mitochondrial function via the PPARs/Nrf2 signaling pathway - Junfang Yuan; Yuzhong Wang; Defeng Wang; Yanfeng Zhen; Yanan Sun; Li Wang; Hui Fang (Metabolic Brain Disease, 2026)

Successional mechanisms of soil bacterial community and its functions driven by rhizosphere habitat and plant growth stages in wetlands - Qingqing Cao; Jiaxuan Zhu; Changchao Li; Jian Liu; Bing Liu; Jiaohui Fang (Applied Soil Ecology, 2026)

Climate change-induced shrub encroachment changes soil hydraulic properties and inhibits herbaceous growth in alpine meadows - Yi-Fan Liu; Hui Fang; Jianjun Shi; Pedro A M Leite; Jingxue Zhao; Gao-Lin Wu (Agricultural and Forest Meteorology, 2023)

Introduction of non‐native fish for aquaculture in China: A systematic review - Bin Kang; Jean R. S. Vitule; Shan Li; Fangmin Shuai; Liangliang Huang; Xiaoxia Huang; Jinghui Fang; Xiaotao Shi; Yugui Zhu; Dongpo Xu; Yunrong Yan; Fangrui Lou (Reviews in Aquaculture, 2023)
Aquaculture, especially of non‐native species and translocated domestic species, is a greatly encouraged way of relieving the conflicts between food and economic demand and resource depletion. We herein summarized the introduction history of non‐native fish for aquacultural use in China, including 105 species introduced from abroad and 61 species translocated domestically across river basins, which has brought great economic benefits but high ecological risks. Of these, one‐fourth have successfully established wild populations in natural waters and 15% have successfully invaded. We presented specific examples of seven aquaculture species/taxa and three aquarium species/taxa to explain their outcomes. The notable economic benefits, complex species composition and strain selection of tilapias, carps and sturgeons may together facilitate their invasion, and result in fish diversity decline, genetic pollution, and loss of ecosystem service. We specifically reviewed invasion cases in lakes and reservoirs and found that lakes in western China and reservoirs made by major hydroprojects are hotspots for non‐native species, and this has led to the disappearance of endemic species and changes to the original faunal composition. The escaped non‐native fish introduced via aquaculture has changed the original fish biogeography, resulting in the loss of assemblage uniqueness and causing faunal homogeneity. China has achieved significant progress in completing the Aichi Targets by improving the legal system and strengthening conservational actions on controlling non‐native species. Further actions, especially on risk assessment and management of non‐native species are expected for a healthy outlook for the aquaculture industry of China.